INFORMATION SYSTEM FOR CURRENCY FORECAST DECISION - Abdul Rosyid; Irwan Bastian, Ir, MM Irwan Bastian, Ir, MM (Jurnal Sistem Informasi, 1998)
Planning is part of an organization. using all the purposes of planning development ina positive direction for the organization can be conducted in accordance with thetarget. inside there is a lot of planning to support a planning tool. One of which is theforecasts (forecasting). Shall be established a system of forecasting information thatwill assist in the planning process. The data exchange prevailing in Indonesia. Dataretrieved from Bank Indonesia is through the newspapers. By studying the varioustheories that support this thesis and consultation with experts, created a system offorecasting information. So that with the end result of a system of useful informationfor decision making to determine policy direction for the organization.